Identification of the major quantitative trait locus cluster qGNPS4.1 for grain number and panicle structure in rice (Oryza sativa). (13th February 2022) - Liu, Jin; Yu, Liqin; Ma, Xiaoding; Zhou, Huiying; Cui, Di; Hu, Jiaxiao; Le, Si; Han, Bing; Chen, Wu; Han, Longzhi; Li, Maomao
Abstract: Panicle structure trait is one of the most important factors affecting yield. Exploring novel regulation genes and clarifying the genetic mechanism have an important meaning to the improvement of rice yield. A recombinant inbred line (RIL) derived from the cross between 'Longdao5' ( Japonica ) and 'Zhongyouzao8' ( Indica ) was used to identify quantitative trait loci (QTLs) for grain number and panicle structure traits under multiple environments. Seventy‐seven QTLs were detected, 21 or 20 of which were stably and reliably detected under two or more than three ecological environments, respectively. These QTLs of the grain number and panicle structure ( qGNPS ) clustered on chromosomes 1, 4, 5 and 10 with pleiotropic genetic overlap effect and stable expression, and then, the major QTL clusters qGNPS4.1 and qGNPS10 were unreported. The novel stable expression major QTL cluster qGNPS4.1 control with grain number and secondary branch number was detected on chromosome 4 under multiple environments. Using the segregating RHL‐F2 and F2:3 population, we narrowed the location of qGNPS4.1 to a 214.94‐kb region. These results will lay the foundation for the major QTL clone and also will enrich the molecular marker‐assisted selection of grain number and panicle structure for molecular breeding in rice.